Предмет: Математика,
автор: СергейГермов
Упростите выражение:
а) -2х(2,5а-1)+5,5а-8.
б)(у+3х)2+(у+3х)(3х-у)
Ответы
Автор ответа:
0
а) -2х(2,5а-1)+5,5а-8= -5ах+2х+5,5а-8
б) (у+3х)2+(у+3х)(3х-у)=у2+2*3ху+9х2 +9х2-у2= 18у2+6ху
б) (у+3х)2+(у+3х)(3х-у)=у2+2*3ху+9х2 +9х2-у2= 18у2+6ху
Похожие вопросы
Предмет: Математика,
автор: 172081977
Предмет: Биология,
автор: slavikovskasasa
Предмет: Физкультура и спорт,
автор: Аноним
Предмет: Математика,
автор: olesaaa110382
Предмет: Литература,
автор: denchik6475